Simultaneous Spectrophotometric Estimation of Norfloxacin and Tinidazole in Two Component Tablet Formulations - Maheshwari, R.K.; Maheshwari, R.B.; Bhatt, P. (Asian Journal of Chemistry, 2010)
Quantitative estimation of poorly water-soluble drugs involves use of organic solvents. Major drawbacks of organic solvents include high cost, volatility and toxicity. In the present investigation, hydrotropic solubilization is employed to enhance the aqueous solubilities of poorly water-soluble drugs norfloxacin and tinidazole in two component tablet formulation for simultaneous spectrophotometric determination. Three simple, accurate and economical procedures employed are program in the multi-component mode of analysis of the instrument used, graphical absorbance ratio method and simultaneous equation method. All methods utilize 8.0 M urea solution as hydrotropic solubilizing agent. In the urea solution, norfloxacin and tinidazole show maximum absorbance at a wavelength of about 274 and 320.5 nm respectively and isobestic point is observed at 297.5 nm. The hydrotropic agent and additives used in the manufacture of tablets did not interfere in the analysis. The results of analysis have been validated statistically and by recovery studies.